Intraperitoneal aerosolization of albumin-stabilized paclitaxel nanoparticles (Abraxane™) for peritoneal carcinomatosis – a phase I first-in-human study - Van De Sande, Leen (Pleura Peritoneum, 2018)
BACKGROUND: Nanoparticles hold considerable promise for aerosol-based intraperitoneal delivery in patients with carcinomatosis. Recently, results from preclinical and early clinical trials suggested that albumin-bound paclitaxel (ABP, Abraxane™) may result in superior efficacy in the treatment of peritoneal metastases (PM) compared to the standard solvent-based paclitaxel formulation (Taxol™). Here, we propose a phase I study of pressurized intraperitoneal aerosol chemotherapy (PIPAC) using ABP in patients with upper Gastrointestinal, breast, or ovarian cancer. METHODS: Eligible patients with advanced, biopsy-proven PM from ovarian, breast, gastric, hepatobiliary, or pancreatic origin will undergo three PIPAC treatments using ABP with a 4-week interval. The dose of ABP will be escalated from 35 to 140 mg/m² using a Bayesian approach until the maximally tolerated dose is determined. The primary end point is dose-limiting toxicity. Secondary analyses include surgical morbidity, non-access rate, pharmacokinetic and pharmacodynamic analyses, quality of life, and exploratory circulating biomarker analyses. DISCUSSION: ABP holds considerable promise for intraperitoneal aerosol delivery. The aim of this study is to determine the dose level for future randomized phase II trials using ABP in PIPAC therapy. TRIAL REGISTRATION: This trial is registered as EudraCT: 2017-001688-20 and Clinicaltrials.gov: NCT03304210.